2012
DOI: 10.1007/s00710-012-0194-x
|View full text |Cite
|
Sign up to set email alerts
|

Cassiterite exsolution with ilmenite lamellae in magnetite from the Huashan metaluminous tin granite in southern China

Abstract: Sn 4+ is generally the dominant form of tin in magnetite-series granites as shown by the presence of cassiterite or its incorporation into Ti-bearing minerals such as biotite and titanite. Little is known about the behavior of tin in magnetite. The Huashan granite is an oxidized tin granite in the Nanling Range, southern China, where it contains magnetite as the dominant Fe oxide mineral. It is included in biotite as an early phase and also as interstitial grains spatially associated with ilmenite, cassiterite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Likewise, the magnetite grains with ilmenite lamellae found in low-grade fenite at Chilwa Island (Figure 2a), may be formed by an 'oxyexsolution mechanism' (Wang et al, 2012;Haggerty, 1991).…”
Section: D1 Mineralising Fluidmentioning
confidence: 99%
“…Likewise, the magnetite grains with ilmenite lamellae found in low-grade fenite at Chilwa Island (Figure 2a), may be formed by an 'oxyexsolution mechanism' (Wang et al, 2012;Haggerty, 1991).…”
Section: D1 Mineralising Fluidmentioning
confidence: 99%
“…On the other hand, higher Sn concentrations in Mag2 (up to 2.82 wt.%) than that in Mag1 indicate that Mag2 was deposited from Sn‐rich fluids. Desborough and Sainsbury () and Wang et al () considered Sn to be incompatible in the evolved magnetite in light of the existence of cassiterite inclusions in magnetite grains. However, experimental studies demonstrated that divalent Sn (Sn 2+ ) could occupy the octahedral sites in the structure of magnetite‐type solid solutions (Hernandez‐Gomez et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Zhao and Zhou () reported high Sn concentrations in magnetite from the Tengtie deposit and interpreted it as Sn incorporation into the magnetite structure. Wang et al () discovered cassiterite exsolution with ilmenite lamellae in magnetite from the Huashan oxidized Sn granite in South China. However, little attention has been paid to the behaviour of Sn in magnetite and the substitution mechanism of Sn for Fe.…”
Section: Introductionmentioning
confidence: 99%
“…In the titanomagnetite system, Sn incorporation is promoted at higher temperatures via vacancy-mediated long-range substitution of Sn ions within boundaries between magnetic domains, albeit with Sn 4+ -Fe 2+ pairs showing lower rates of diffusion than Ti 4+ -Fe 2+ pairs in magnetite (Hernández-Gómez et al, 2001, 2006. An example of cassiterite particles attached to ilmenite lamellae has been shown for magmatic titanomagnetite (Wang et al, 2012).…”
Section: Exsolutions From Solid Solution: Mg-si Defects Predating Sn-...mentioning
confidence: 99%
“…A comparable approach can be undertaken for Sn-bearing magnetite. Tin, exsolved as cassiterite inclusions in magnetite has been long recognized from micron-scale investigations (Desborough and Sainsbury, 1970;Wang et al, 2012;Wang et al, 2018). Although published data show that average Sn concentrations in magnetite are generally no more than a few tens of ppm (e.g., Nadoll et al, 2014), concentrations commonly reach hundreds and even thousands of ppm in relatively Sn-rich systems (e.g., Huanggang Fe-Sn skarn, China; Mei et al, 2014;Olympic Dam IOCG, Australia,Verdugo-Ihl et al, 2020).…”
Section: Introductionmentioning
confidence: 99%